THE DEVELOPMENT OF MISS PPL (ADVANCED MICROSOFT POWER POINT) LEARNING MEDIA AT ELEMENTARY SCHOOL - Liza Auliya; Lazim N (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This research aims to develop, know the feasibility test, and see teacher responses and student responses to Miss PPL (Advanced Microsoft Power Point) learning media at elementary school. The media was developed by using Microsoft Power Point 2010 applications. The research method used was a development method with an ADDIE model (Analysis-Design-Develop-Implement-Evaluate). The data obtained were analyzed descriptively quantitative. The result of this study obtained information about the feasibility of the product assessed by the validator from 86.26 with highly feasible category in draft 1 increasing to 95.57 with highly feasible category in draft 2. Teacher response data was 84.38 with a very good category and student responses score 95.89 with a very good category. Based on the result of the research, it can be concluded that Miss PPL learning media (Advanced Microsoft Power Point) developed is suitable for use and increases the diversity of social science learning media, especially in the diversity of Indonesian society.